Pulse oximetry screening for critical congenital heart disease - Experience in a public hospital in India - Palve, Nandkishor; Utture, Alpana; Nanavati, Ruchi; Hire, Akshay; Kerkar, Prafulla (Indian Journal of Child Health, 2022)
Background: Critical congenital heart disease (CCHD) if undiagnosed in the first few days of life is associated with high morbidity or and mortality. Pulse oximeter screening for CCHDs in newborn babies can aid in early recognition with the prospect of improved outcome. Routine pulse oximetry screening of asymptomatic infants for CCHD is prevalent in developed countries but not in India. Aims: To estimate the diagnostic accuracy of screening for CCHD with a new generation pulse oximeter in a setting of a public hospital in India. Materials and Methods: A prospective observational study including all term neonates (>37 weeks) admitted to the postnatal ward. Results: 1594 term newborns were screened by pulse oximetry. Of these, 1589 (99.69%) neonates passed the screening and 5 failed the test. For CCHD, sensitivity was found to be 100% with a specificity of 99.94% and positive and negative predictive value was 80% and 100%, respectively. Peripheral perfusion index (PPI) was 2.04 in infants who passed the test in comparison to 0.65 in those who failed the test. Conclusion: Pulse oximetry has a high sensitivity, specificity, and negative predictive value for detection of CCHD in newborn infants. PPI is a good predictor of systemic hypoperfusion in CCHD.